2023
DOI: 10.23887/jere.v7i3.60532
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Students' Difficulties in Learning Mathematics in Complex Variable Material

Jitu Halomoan Lumbantoruan

Abstract: Prospective mathematics teachers are required to be able to master facts and be able to give examples that exist in everyday life. A prospective mathematics teacher is expected to be skilled and mature in using media when operating, explaining and demonstrating direct objects that exist in any complex variable material. The aim of this study is to analyze the obstacles and difficulties of students in Mathematics. Two indicators for assessing mathematics learning outcomes: 1) Direct objects (Facts, Concepts, Sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 69 publications
0
1
0
1
Order By: Relevance
“…Beberapa studi terdahulu telah menjelaskan bahwa matematika dianggap sebagai sebuah pelajaran yang membosankan dan kurang diminati oleh para siswa. Kurangnya minat siswa terhadap matematika juga terlihat dari hasil belajar siswa yang cenderung tidak memuaskan dalam mata pelajaran ini (Lumbantoruan, 2023). Matematika juga dianggap mata pelajaran yang sulit bagi sebagian besar siswa, dimana banyak siswa yang setelah belajar matematika namun tidak mampu memahami apa yang diajarkan bahwa tentang bagian yang sederhana.…”
Section: Pendahuluanunclassified
“…Beberapa studi terdahulu telah menjelaskan bahwa matematika dianggap sebagai sebuah pelajaran yang membosankan dan kurang diminati oleh para siswa. Kurangnya minat siswa terhadap matematika juga terlihat dari hasil belajar siswa yang cenderung tidak memuaskan dalam mata pelajaran ini (Lumbantoruan, 2023). Matematika juga dianggap mata pelajaran yang sulit bagi sebagian besar siswa, dimana banyak siswa yang setelah belajar matematika namun tidak mampu memahami apa yang diajarkan bahwa tentang bagian yang sederhana.…”
Section: Pendahuluanunclassified
“…In 2022, the number of students in the Science (Velazco et al, 2022), Mathematics, and Technology pathway will be 43.18%, indicating that students still fail to master mathematics well, and this has an impact on science and technology abilities, considering that the selection requirements for the Science and Technology pathway require a good foundation in mathematics (Lumbantoruan & Male, 2022). In research Lumbantoruan & Manalu, (2024) students were found in surveys to have low learning outcomes in mathematics learning motivation. The ability to master mathematics requires learning techniques, knowledge, and determination.…”
Section: Problem Statementmentioning
confidence: 99%